Design of Supply Chain Performance Evaluation for CV Jumjum Station - Fatimah Kalitdyah; Handayani, Wiwik (AFEBI Management and Business Review, 2024)
Efficient supply chain performance is a critical factor for a company's success. This research aims to design a supply chain management (SCM) performance evaluation system using the Balanced Scorecard (BSC) approach as a basis for determining Key Performance Indicators (KPIs) at CV Jumjum Station. The research method employed is descriptive quantitative, with primary data collected through interviews, pairwise comparison questionnaires, and secondary data from literature studies. Data analysis is conducted using the Analytic Network Process (ANP) using Super Decision 3.20 to measure the level of importance among hierarchies and BSC perspectives. The results indicate that the financial aspect is the top priority in evaluating SCM performance, followed by employee development, customer service, and the company's internal processes. Delivery reliability, product development, and productivity ratios are identified as key areas that need improvement to optimize the company's SCM performance.